2019
DOI: 10.31195/ejejfs.568822
|View full text |Cite
|
Sign up to set email alerts
|

A faunistic study on the geometrid moths (Lepidoptera) of Maden (Elazığ) district

Abstract: This paper is conducted on the Geometridae fauna of Maden (Elazığ) district. In total, 87 species are diagnosed in 47 genera of 6 subfamilies. Except Charissa onustaria (Herrich-Schäffer, [1852]), all of the determined species are new record for the research area and also 81 of the species are new record for Elazığ province. And, second location records of rare known species,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Hostplants: Pittaway [3], Akkuzu et al [12]. Distribution in Turkey: Akkuzu et al [12], Gözüaçık et al [16], Koçak and Kemal [18], Ünlü and Kornoşor [22], Seven and Çakır [17], Seven [15], Tiftikci and Kornoşor [23], Kemal and Seven [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hostplants: Pittaway [3], Akkuzu et al [12]. Distribution in Turkey: Akkuzu et al [12], Gözüaçık et al [16], Koçak and Kemal [18], Ünlü and Kornoşor [22], Seven and Çakır [17], Seven [15], Tiftikci and Kornoşor [23], Kemal and Seven [24].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 96 taxa are known in the western Palearctic region [3]. In the Turkish fauna, 36 species are known in this family [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][22][23][24]: Acherontia atropos (Linnaeus, 1758); Agrius convolvuli (Linnaeus, 1758); Akbesia davidi (Oberthür, 1884); Clarina kotschyi (Kollar, [1849]); C. syriaca (Lederer, 1855); Daphnis nerii (Linnaeus, 1758); Deilephila elpenor (Linnaeus, 1758); D. porcellus (Linnaeus, 1758); D. suellus Staudinger, 1878; Dolbina elegans A. Bang-Haas, [1913]; Hemaris croatica (Esper, [1779]); H. tityus (Linnaeus, 1758); H. dentata (Staudinger, 1887); H. syra (Daniel, 1939); Hippotion celerio (Linnaeus, 1758) On the Sphingidae family, limited number of investigations have made in the east and southeast of Turkey. The majority of the studies carried out in recent years in the region are as follows: Ünlü and Kornoşor [22] reported that Sphingidae family is represented by 10 species in Şanlıurfa province.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identification and distribution of the species, the sources utilized are include: Wagner (1929Wagner ( , 1930Wagner ( , 1931; Kansu (1963); Freina & Hermann (1985); Freina & Witt (1987); Varga & Ronkay (1991); Fibiger (1997); Ronkay et al (2001); Hacker et al (2002); Zilli et al (2005); Leraut (2006Leraut ( , 2012; Fibiger & Hacker (2007); Koçak & Kemal (2007); Fibiger et al (2009;; Seven (2014); Kemal & Koçak (2017); Koçak & Kemal (2018); and Seven & Çakır (2018).…”
Section: Methodsmentioning
confidence: 99%
“…And following, they were reported 243 moth species in the latest current article ''A synonymous and distributional list of the species of the Lepidoptera of Turkey'' in 2018 (Koçak & Kemal, 2018) from Elazığ Province. Seven & Çakır (2018)…”
Section: Introductionmentioning
confidence: 99%